Autogenous transplantation of maxillary and mandibular molars - Maha Mortaga Mohamed Negm; Khaled Atef Elhayes; Mohamed Galal Beheiry; Sameh Seif (Cairo : Maha Mortaga Mohamed Negm, 2012)
To evaluate the validity and reliability of the autogenous transplantation of maxillary or mandibular molars . Ten patients received either a mandibular or maxillary third molar to replace a non restorable mandibular first or second molar . The clinical parameters were mobility and probing pocket depth . Rediographic assessment of progress of root development , periapical or periodontal radiolucencies
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Oral and Maxillofacial Surgery
Issued also as CD
Keywords: Autogenous transplantation; Immature root; Third molars